2000
DOI: 10.1002/1521-3773(20001215)39:24<4488::aid-anie4488>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Structure Determination of an Oligopeptide Directly from Powder Diffraction Data

Abstract: A direct‐space strategy, in which global optimization is carried out on the Rwp hypersurface using a genetic algorithm combined with local minimization of Rwp, has been used to solve the crystal structure of the oligopeptide Phe‐Gly‐Gly‐Phe directly from powder X‐ray diffraction data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 29 publications
0
16
0
2
Order By: Relevance
“…Recently, the structure determination of the oligopeptide Phe‐Gly‐Gly‐Phe from powder diffraction data has been reported 84. The structure was solved using a modified version85 of the genetic‐algorithm technique, based on Lamarckian evolution (discussed in Section 5.3.4).…”
Section: Examples Of Structure Determination From Powder Diffractimentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the structure determination of the oligopeptide Phe‐Gly‐Gly‐Phe from powder diffraction data has been reported 84. The structure was solved using a modified version85 of the genetic‐algorithm technique, based on Lamarckian evolution (discussed in Section 5.3.4).…”
Section: Examples Of Structure Determination From Powder Diffractimentioning
confidence: 99%
“…The possibility of using genetic‐algorithm techniques in structure solution from powder diffraction data was realized independently by two research groups. Our approach46, 48, 49, 53, 57, 72, 84, 85, 171, 172 and the approach of Shankland, David and coworkers47, 71, 173 differ in the definition and handling of the fitness function, as well as other aspects of the way in which the genetic algorithm is implemented. Details can be found in the papers cited.…”
Section: Overview Of Techniques Used In Structure Determination Frmentioning
confidence: 99%
“…Kürzlich wurde die Bestimmung der Struktur des Oligopeptids Phe‐Gly‐Gly‐Phe aus Pulverbeugungsdaten beschrieben 84. Zur Strukturlösung wurde eine modifizierte, auf einer Lamarckschen Evolution basierenden Version85 des genetischen Algorithmus verwendet (sie wird in Abschnitt 5.3.4 behandelt).…”
Section: Beispiele Zur Strukturbestimmung Aus Pulverbeugungsdatenunclassified
“…This is reflected in the Cambridge Structure Database (CSD version 5.35, November 2013 release) search conducted among the organic solids, which revealed that out of total 675 301 entries only 1459 (~0.22%) structures have been solved from X‐ray powder data (including both laboratory and synchrotron X‐ray data) without referring to an isotopic single crystal structure. If we restrict our search to acyclic synthetic peptides, then out of 2454 hits, only six examples such as, H 2 + ‐Phe‐Gly‐Gly‐Phe‐O − , Piv‐Pro‐γ‐Abu‐NHMe , Piv‐Pro‐Gly‐NHMe , Bzl‐CH(COOEt)‐Ala‐Pro‐OH , H‐Asp‐Phe‐OMe and Ac‐Tyr‐Glu‐Gln‐Gly‐Leu‐NH 2 are found, whose structures have been solved from X‐ray powder diffraction.…”
Section: Introductionmentioning
confidence: 99%